Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2023)
Table of Content 1. The impact of strategic leadership on improving the organizational health of Yemeni private universities Co-Prof. Zayed Naji Shawesh, Mr. Abdullah Ahmed Al-Shakhfir 2. The role of transformational leadership in promoting social responsibility (Applied study on Directorate of Health Affairs in Aseer) Mr. Abdullah Mubarak Said Alkhudran 3. The validity of electronic evidence in Omani law Mr. Hamad Salem Hamad Al-Alawi 4. The Effect of Job Burnout Stability (Applied Study on the Health Sector in Asir Region in KSA- 1444AH) Mrs. Asma Mohamed Al-Shehri, Mrs. Reem Awad Abo Dahesh, Mrs. Sara Hussein Al Sultan, Mrs. Bayan Abdullah Asiri , Mrs. Jamilah Salman Al-Maliki 5. Functions of the criminal investigation authority in the Saudi partial Criminal procedure System Dr. Yasmeen Ahmad Mohammed 6. The Impact of the Work Environment and Services on the Degree of Job Satisfaction of Faculty Members A field Study at Nile Valley University – Sudan (2021 – 2022 AD) Dr. Omer Mustafa Ali Osman 7. Purchase Intentions and Luxury Brands: A Study on Consumer Behaviour in Saudi Arabia Mrs. Nora Toffaha, Prof. Maha Abdullah Al-Dabbagh